Investigation of architecture of contemporary monitoring systems In cellular networks - Одарченко, Р. С.; Коберник, А. Ю.; Федюра, Т. В. (Science-based technologies, 2018)
In this paper, OSS solutions (Operations Support Systems) are investigated that allow to increase the efficiency of operational processes of planning, construction and operation of the network of telecom operators, and also enable engineers to perform their work faster, more efficiently and better. Providing a given level of service quality and high availability of network equipment is one of the key tasks of the telecommunications operator. It has been analyzed that the rapid detection of faults, the effective search for causes and the determination of priorities in their elimination are critical for the effective achievement of this goal. It has been revealed that in companies and organizations that use disparate monitoring tools, there is no unified view of the network, and as a consequence of the impact of an event on the quality of service provision. Operational diagnostics and the detection of emergencies are quite complex tasks that can be solved only by a set of organizational and technical activities. The introduction of the operational support system allows, first of all, to shorten the time to identify possible problems that can lead to malfunctions in the operation of equipment and information systems. Umbrella Fault Management allows you to tie everything together and organize management from a single console.